Evaluation of Mindfulness Intervention on Self-Efficacy in Stunting and Non-Stunting - Zakiah; Yuniarti; Agustine Ramie; Sujiyanti; Yuli Suryanti (Jurnal Penelitian Pendidikan IPA, 2025)
Stunting remains a significant public health problem in Indonesia, while interventions to improve maternal self-efficacy are urgently needed. This study aims to evaluate the effectiveness of mindfulness interventions on maternal self-efficacy in mothers with stunting and non-stunting toddlers. This study adopted a quasi-experimental design to explore the impact of a mindfulness intervention on two groups of mothers: mothers of stunted (n=15) and non-stunted (n=15) children. The structured intervention involved mindfulness sessions that included guided relaxation and mindful parenting practices. Data collection was conducted using a validated self-efficacy questionnaire. Statistical analysis included Shapiro-Wilk normality testing and paired t-tests to evaluate differences in pre- and post-intervention scores, as well as Pearson correlation analysis to understand the relationship between pre- and post-intervention scores. The analysis showed that the stunting group had larger families, which could indicate an imbalanced allocation of nutritional resources. Meanwhile, the t-test results showed a significant increase in maternal self-efficacy scores from the stunting group after the mindfulness intervention, from 104.87 (SD = 14.16) to 111.47 (SD = 12.81), with a p-value of 0.011. The study concluded that the mindfulness intervention can serve as an effective support strategy in childcare programs to address stunting issues.